Analisis Pengaruh Pendidikan Kewirausahaan dan Kecerdasan Adversitas terhadap Intensi Berwirausaha Mahasiswa - Santi Rohmah; Maria Aghata Sri Widya (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2020)
The purpose of this study was to determine the effect of entrepreneurship education and adversity intelligence on the entrepreneurial intentions of students of University Bhinneka PGRI. The population of this study 41 students and the instrument used was a questionnaire. The sampling technique used is saturation sampling. Data analysis in this study used multiple linear regression. The result of this study indicates that there is a positive and significant effect between entrepreneurship education on entrepreneurial intentions with a tcount (2,153) > ttable(2,020) and a significant value of 0,038 < 0,05. Adversity intelligence has a positive and significant effect on entrepreneurial intentions with a tcount (2,215) > ttable(2,020) and significant value of 0,033 < 0,05. While simultaneously there is a positive and significant effect between entrepreneurship education and adversity intelligence on entrepreneurial intentions whit a value a fcount(31,216) > ftable (3,23) with a significant level of 0,000 <0,05. The coefficient of determination of this amounted to 0,602. It can be concluded that this study 60,2% is influenced by entrepreneurship education and adversity intelligence. While the remaining 39,8% is influenced by other variables